Capital Structure and Corporate Governance of Consumer Non-Cylicals Companies : Mediating Corporate Performance - Puri Asih, Laras; Musa Budidarma , I Gusti Agung (Asian Journal of Social and Humanities, 2023)
This research aims to determine the influence of capital structure and corporate governance on share prices, mediated by company performance in non-cyclical consumer companies listed on the IDX for the 2020 - 2022 period. The data collection technique was purposive sampling with a sample of 51 non-cyclical consumer companies listed on the IDX for the 2020-2022 period. Testing in this research was carried out with the Eviews 9 software program. The research results prove that capital structure as measured by DAR has a negative and significant effect on share prices. Apart from that, DER has a positive and significant effect on company performance, while what is measured by DAR has a negative and significant effect on company performance. Corporate governance as measured by KP has a negative and significant effect on company performance. Company performance does not mediate the influence of capital structure and corporate governance on share prices. The sample period used is 2020 - 2022 and the role of company performance in mediating capital structure and corporate governance on share prices. For non-cyclical consumer companies that have go public, it is hoped that they will pay more attention to the DER, DAR and KP ratios, which are an illustration of capital structure and corporate governance which have been proven to have a significant influence on company performance. Apart from that, the DAR ratio is also a description of the capital structure which has been proven to have a significant effect on share prices